Uganda Local Government Councils Score Card Report 2009/10: Political Accountability, Representation and the State of Service Delivery - Tumushabe, Godber W.; Muyomba-Tamale, Lillian; Ssemakula, Eugene (ACODE Policy Research Series, 2011)
The Local Government Councils’ Score-card is an innovative action-research initiative that assesses the performance of local government councils in Uganda. This report presents finding of the second score-card covering the FY2009/10. The report builds on the first local government councils score-card report first published in 2010 covering 10 districts. The 2009/10 score-card covers a total of 20 districts evenly distributed across Uganda and selected based on standard criteria. The score-card assesses the performance of local government councils and their respective organs that comprise the district chairperson, the district speaker and the individual councilors. The council is also assessed as a cooporate body. These organs are assessed on mainly four issues which are part of the core mandate of the local governments under the Local Government Act. These include: financial management and oversight; political functions and representation; legislative, legislation and related functions; development planning and; constituency servicing and monitoring service delivery. The score-card methodology combines the literature review, inception meetings, interviews and focus group discussions as the primary approaches for collecting data and information on the performance of district councils. The approach ensures the participation of councilors and other interest groups in conducting the assessment. In this regard, the score-card is a living document with the flexibility to evolve and develop over time and be able to incorporate adjustments along the way